Comparison of contrast enhanced ultrasound with dextrose 50% and normal saline in detecting supradiaphragmatic central venous catheter malposition - Iberahim, Nor Afifah (2023)
ABSTRACT Background: Chest radiograph is performed after insertion of a central venous catheter to confirm its placement. However, this standard procedure delays catheter usage, exposing patients to radiation with added cost. Contrast-enhanced ultrasound (CEUS) using normal saline has been used in most previous literature as an alternative to chest radiograph. Recent studies have then explore the suitability of dextrose 50% as a contrast agent. It has been proven to generate a better ultrasonic image than normal saline to detect congenital heart condition such as patent foramen ovale. Hence, this study aims to demonstrate if this finding can significantly affect CVC malposition detection. We would like to investigate the possible difference between dextrose 50% and normal saline in detecting CVC malposition. Methods: This is a cross-sectional study using convenient sampling. Subjects were chosen from the in-patient ward HUSM, who were indicated for central venous catheter insertion. We compared catheter malposition detection using dextrose 50% and normal saline as contrast agent by the observation of Rapid Atrial Swirl Sign (RASS) characteristic into the right atrium. Chest radiograph is used as the standard reference to confirm correct CVC position. Results: From the 99 patients included in this study, 7 CVC malpositions were confirmed by chest radiograph. Only 1 of these malpositions was detected by both contrast agents. There was a poor agreement between both dextrose 50% (k = 0.049) and normal saline (k = 0.078) with chest radiograph. The sensitivity for both contrasts to detect CVC malposition was 14% with a specificity of 97.5%. Conclusion: Normal saline and dextrose 50% are equivalent as contrast agents to detect CVC malposition. Both have a poor agreement with the chest radiograph. Chest radiograph is still indicated to confirm CVC malposition, but CEUS can be a useful tool to confirm the intravenous position of the catheter to facilitate its earlier usage.